Fluoride in drinking water and associated non-carcinogenic health risk in Inner Mongolia Autonomous Region, 2022: a monitoring data analysis - Wenqian ZHANG; Jiake ZHU; Wenyu ZHANG; Xinrui JIA; Xuanzhi YUE; Huan LI; Duoduo WU; Yuhan QIN; Yaochun FAN (Zhongguo gonggong weisheng)
ObjectiveTo investigate the fluoride content of drinking water and the non-carcinogenic health risk of oral fluoride exposure in the Inner Mongolia Autonomous Region (Inner Mongolia) in 2022 by analyzing monitoring data for the management of drinking water hygiene in the region. MethodsA total of 7 488 surface/underground resource and treated/secondary supplied/tap water samples were collected in dry and wet seasons from domestic drinking water monitoring stations located in different river basins and urban/rural areas in 12 municipalities of Inner Mongolia in 2022; fluoride in the samples was detected and analyzed. The non-cancer health risk associated with oral exposure to fluoride in drinking water was evaluated using the United States Environmental Protection Agency's (USEPA) four-step approach. ResultsFor all samples, the fluoride concentration (mg/L) ranged from not detected to 8.830, with a median of 0.500 and a 25th/75th percentile of 0.300/0.750; the fluoride content in 91.64% of the samples was within the limit (≤ 1.0 mg/L) of the National Sanitary Standards for Drinking Water (GB 5749 – 2006). For all water samples, the non-carcinogenic hazard quotient (HQ) associated with oral exposure to fluoride in drinking water was 0.31 for the adult population, and 2.18% (163) of the samples had HQ values greater than 1. For children and adolescents, the non-carcinogenic HQ increases and then decreases with age, with the highest HQ (0.45) for children aged 1 – < 2 years and some samples with HQ greater than 1 for children and adolescents of different ages. The non-cancer health risk of oral fluoride exposure was similar for male and female adults (HQ = 0.31), and the non-cancer health risk was higher (HQ = 0.33 – 0.45) for children aged 9 months – < 3 years than for adults. There were significant differences in fluoride content and associated non-cancer health risk for samples collected from different river basins (H = 648.781，P < 0.001); the fluoride content and associated non-cancer health risk (HQ = 0.40) were the highest for samples from the Liaohe River basin, followed by those from the basins of some inner rivers (0.37), Haihe River basin (0.36), Yellow River basin (0.26), and Heilongjiang River basin (0.24), respectively. The qualification rate (fluoride content lower than the national standard of ≤1.0 mg/L) of water samples from urban areas was higher than that from rural areas (95.96% vs. 89.58%, χ2 = 87.077; P < 0.001), and the qualification rate of groundwater samples was higher than that of surface water samples (99.72% vs. 91.23%, χ2 = 32.146; P < 0.001); both the fluoride content and the associated non-cancer health risk of surface water samples were lower than those of groundwater (0.340 mg/L vs. 0.500 mg/L, 0.21 vs. 0.31, Z = – 11.761; P < 0.001). There were significant differences in fluoride content and associated non-carcinogenic health risk among treated/secondary supplied/tap water samples (H = 55.551, P < 0.001), with higher fluoride content (0.530 mg/L vs. 0.490 mg/L) and associated non-carcinogenic HQ (0.33 vs. 0.30) of treated water than that of tap water samples (P < 0.001). ConclusionsThe non-carcinogenic health risk associated with exposure to fluoride in drinking water in the Inner Mongolia Autonomous Region in 2022 exceeds the maximum acceptable risk recommended by the USEPA, and the situation should be addressed in drinking water-related health risk management.